The Effect of Customer Gratitude as Mediation in The Relationship of Marketing Investments on Behavioral Loyalty - Mohammad Sofwan Effendi; Dewi Agustin Pratama Sari (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2020)
This research aims to examine the effect of marketing investments conducted by binder manufacturers such as direct mail, tangible rewards, interpersonal communication, and preferential treatment towards behavioral and customer gratitude as mediator variables. This research is a quantitative study with 95 respondents from binder manufacturers. The sampling technique used is the convenience sampling technique. The data that has been obtained is processed using the IBM SPSS Statistics 20 for Windows program. Based on this research, marketing investments such as direct mail, tangible reward, and preferential treatment have a significant relationship with the variable customer gratitude. Besides, interpersonal communication activities do not have a substantial effect on customer gratitude. Preferential treatment by binder producers has the most significant positive impact on customer gratitude than other marketing investment variables. Finally, it is also known those customer gratitude customers due to the effect of marketing investment activities by binder manufacturer influence customer behavioral loyalty.